Distribuição de macroinvertebrados, com ênfase no gênero Hyalella (Crustacea: Peracarida: Amphipoda), em ambientes lênticos e lóticos do sul do Brasil - Antunes, Michelle Bicalho (2015)
Aquatic environments have been altered due to the increase of anthropogenic activities. The degradation of aquatic ecosystems has reached alarming levels, particularly in freshwater ecosystems. Water resources monitoring and evaluation, using biotic indices contribute to a better understanding of ecological processes and conditions of aquatic ecosystems. Macroinvertebrates are the most tested and used group for bioindication studies in water resources. Crustaceans are among the most representative invertebrates in freshwater environments. Amphipoda is among the most significant orders, housing the Hyalellidae family and the Hyalella genus, which is the only genus of amphipod crustaceans found in Brazilian limnic environments. Brazil is the American country with the highest diversity of Hyalella genus (Crustacea). However, ecological studies with this genus in the country are rare. In this context, this study aims to analyze the structure of freshwater macroinvertebrate communities, with emphasis on the Hyalella genus, between lotic and lentic (natural and artificial) environments, in the central region of the Rio Grande do Sul State as well as to identify the influence of environmental variables on the structure of these communities. Samples were taken from 105 watercourses (weir, puddle and stream) covering all cities in the central region of the Rio Grande do Sul State. Water physical and chemical parameters were measured in each sample point. 26,181 individuals belonging to 40 taxa were sampled. Hyalella was the most abundant genus, with 14,601 individuals. Puddles were the environments with the highest abundance of macroinvertebrates. Environmental variables differed among lentic and lotic environments and this variation interfered in the macroinvertebrates distribution. Artificial lentic environments could represent a conservation alternative, presenting essential responsibility for the preservation of taxa that occur in lentic natural environments and lotic environments. Variations within the same environment is not what, in fact, appears to interfere and explain the presence and abundance of Hyalella, but the variation between environments (natural and artificial lentic and lotic) seems to determine the presence and abundance of the genus. There was also a strong influence of the environment on the occurrence/distribution of Hyalella species identified for the sampled region, and the weir may be playing an important intersection area between puddle and stream. Two species were identified, Hyalella bonariensis and Hyalella curvispina, which were already known to the state of Rio Grande do Sul and six morphospecies, which are likely to be new to science. Since freshwater environments are highly threatened ecosystems, studies addressing its operation and biodiversity maintenance will contribute significantly to the preservation of these areas, providing support for future conservation programs.